Social Status and Group Norms - Ingrid Seinen; Arthur Schram (Tinbergen Institute, 2001)
This paper provides experimental evidence showing that indirectreciprocity may important in economic decision making and in thedevelopment of group norms. We study a `repeated helping game' withrandom pairing in large groups, with individuals equally dividedbetween donors and recipients. Donors decide whether to help theindividuals they are matched with against a certain cost or not tohelp, enduring no costs. We observe that many decision makers respondto the information we give them about former decisions of therecipients, even if they realize that this information is based ontransactions with third parties.
Keywords: C92; 330; Sozialer Status; Gruppenentscheidung; Test; Theorie